Benefits of three-month continuous glucose monitoring for persons with diabetes using insulin pumps and sensors - Peterson, Karolina; Zapletalova, Jana; Kudlova, Pavla; Matuskova, Veronika; Bartek, Josef; Novotny, Dalibor; Chlup, Rudolf (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2009)
BACKGROUND: The latest Paradigm 722 insulin pump, Medtronic MiniMed, USA, enables daily reading of 288 interstitial fluid glucose concentrations determined by a sensor inserted into subcutaneous tissue; the sensor signals are transmitted into the insulin pump, enabling the patient to see real-time glucose concentration on the display and adapt further treatment. AIMS: To assess the evolution of HbA1c over the course of a 3-month period in two cohorts of persons with type 1 (n=39) or type 2 (n=3) diabetes (PWD): 1) PWD on Paradigm 722 using sensors for continuous glucose monitoring (CGM group), 2) PWD on other types of insulin pumps performing intensive self-monitoring as before (3 to 6 times/d) on glucometer Linus, Wellion, Agamatrix (control group). METHODS: Compliant PWDs using insulin pump with insulin aspart for several previous months were included in the study. Seventeen were put on Paradigm 722 with CGM and 25 were included in the control group. Paired t-test and the statistical program SPSS v.15.0 were used to analyze the data. RESULTS: There was no significant difference in age between the two groups (P=0.996), in diabetes duration (P=0.482) or in daily insulin dose (P=0.469). In the CGM group (but not in the control group) HbA1c/IFCC dropped from 6.98+/-0.43 % to 5.98+/-0.36 % (P=0.006) within 1 month and remained reduced. CONCLUSION: The use of the Paradigm 722 insulin pump with CGM resulted in significant improvement in HbA1c which appeared within one month and remained throughout the whole 3-month study period. No significant improvement in HbA1c was seen in the control group.
Keywords: diabetes mellitus; Diabetes Mellitus; Male; glykovaný hemoglobin; ambulantní monitorování; inzulinové infuzní systémy; Monitoring, Ambulatory; biosenzitivní techniky; krevní glukóza; Adult; Aged; dospělí; mužské pohlaví; senioři; Biosensing Techniques; lidé; ženské pohlaví; Glycated Hemoglobin; Humans; Glycated Hemoglobin A; Female; Blood Glucose; lidé středního věku; Middle Aged; Insulin Infusion Systems